Homophily in higher education: Historicizing the AERA member-to-fellow pipeline using theories of social reproduction and social networks. (September 2017) - Hartlep, Nicholas D; Hensley, Brandon O; Wells, Kevin E; Brewer, T Jameson; Ball, Daisy; McLaren, Peter
This study examines select demographics of the American Educational Research Association (AERA) Fellows ( n = 644), and whether or not the cohorts of AERA Fellows are becoming more diverse in racial and gender terms in relation to the inaugural year of Fellows in 2008. This study tests the mission statement of this exclusive program to '… recognize excellence in research and be inclusive of the scholarship that constitutes and enriches education research as an interdisciplinary field'. Our findings suggest that homophily – a sociological phenomenon that describes the ways in which individuals and institutions prefer sameness – is a real problem in higher education, and programs such as the AERA Fellowship are not accomplishing their mission to recognize the research of faculty of color, women faculty, and faculty in interdisciplinary fields. In contrast to the AERA Fellows mission statement, we find that the Fellowship program relies on homophilous social networks in selecting AERA Fellows and, in turn, reinforces social reproduction in higher education.